1999
DOI: 10.2134/agronj1999.915834x
|View full text |Cite
|
Sign up to set email alerts
|

Corn Hybrid Response to Planting Date in the Northern Corn Belt

Abstract: Growers frequently are concerned about the response of corn (Zea 1968). The optimum planting date in the Corn Belt mays L.) to planting date. Early planting of corn is recommended because full-season hybrids utilize the entire growing season, achieve typically occurs between 20 April and 10 May (Benson, physiological maturity before a killing frost, and start to dry, thereby 1990). While some studies show an advantage for plantincreasing profit through reduced drying costs. The objective was to ing before 20 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
114
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 8 publications
10
114
3
2
Order By: Relevance
“…Site-years planted between late April and mid-May yielded higher than site-years planted after mid-May (11.4 compared to 10.3 Mg ha -1 ). This is consistent with the results of Lauer et al (1999) who reported that grain corn yields decreased with later planting date. In our study, the increase in yield between the two groups of site-years could be explained by the planting date (Mullen et al, 2010), but other parameters such as soil types, hybrids and weather conditions may be involved (Almaraz et al, 2008;Ziadi et al, 2013;Tremblay et al, 2012;Woli et al, 2016).…”
Section: Site Id Yearsupporting
confidence: 93%
“…Site-years planted between late April and mid-May yielded higher than site-years planted after mid-May (11.4 compared to 10.3 Mg ha -1 ). This is consistent with the results of Lauer et al (1999) who reported that grain corn yields decreased with later planting date. In our study, the increase in yield between the two groups of site-years could be explained by the planting date (Mullen et al, 2010), but other parameters such as soil types, hybrids and weather conditions may be involved (Almaraz et al, 2008;Ziadi et al, 2013;Tremblay et al, 2012;Woli et al, 2016).…”
Section: Site Id Yearsupporting
confidence: 93%
“…Moreover, delayed sowing increases the probability of early autumn freezing occurring at latter stages in maize growth, thereby restraining grain maturity and leading to output reduction [12,13]. Early planting with film mulching is regarded as an effective measure to increase production against the cold, because despite crop exposure to a low-temperature environment at the prophase, the growth point is not endangered; besides, no adverse effect was observed in middle-later stages, and maize can reach physiological maturity before early autumn freezing occurs [14,15].…”
mentioning
confidence: 99%
“…Salah satu strategi untuk mengantisipasi ketidakpastian awal musim dan kejadian iklim ektrem adalah dengan menyesuaikan waktu tanam (Lauer et al 1999). Untuk mengatur waktu tanam dan panen, berbagai negara menggunakan kalender tanam (Sacks et al 2010;AMIS 2012).…”
Section: Kalender Tanamunclassified